REFLECTIONS FROM UPRISING: THE ROLE OF YOUTH AND SOCIAL MEDIA IN POLITICAL MOVEMENTS IN NEPAL AND INDONESIA - Md. Yeasir Arafat; Md. Sobuj Mia; Md. Ismail Hossen Imran; MD. Rafiul Islam (CV. Tirta Pustaka Press, 2025)
While youth-led digital activism is increasingly visible across the globe, scholarly understanding of how these dynamics shape political outcomes in South and Southeast Asia remains limited. Addressing this gap, this study investigates how Generation Z in Nepal and Indonesia employs social media to mobilize political action and influence institutional change. Specifically, the research compares the mechanisms through which online platforms facilitate coordination, amplify grievances, and construct collective identity among young activists in both countries. Using a qualitative comparative approach that integrates media content analysis with secondary data from reports and news archives, the study analyzes two key cases: the 2025 social-media-ban protests in Nepal and the digitally driven mass demonstrations in Indonesia. The findings show that digital activism not only accelerates the transition from online engagement to offline mobilization but also generates cross-border ripple effects, where successful youth movements inspire similar actions in neighboring states. This study contributes to a deeper understanding of youth political agency in the digital era and offers insights into the evolving patterns of civic engagement shaped by social media.